The effectiveness of the Dutch juvenile diversion program Halt: study protocol for a randomized controlled trial - Benthe J. van Delft; Kirti Zeijlmans; Jessica J. Asscher; Ton Liefaard; André M. van der Laan (BMC Psychology)
Abstract Background Halt (acronym for ‘The Alternative’ in Dutch) is the most widely used youth justice diversion measure for juveniles (12 up to and including 17 year olds) in the Netherlands. Therefore, it fits well with international children’s rights. Halt gives juveniles the opportunity to learn from their mistake and avoid a criminal record. The goal of Halt is to reduce recidivism by working on several subgoals. These subgoals consist of cognitive behavioral mechanisms, such as improving social skills and enhancing feelings of responsibility for (delinquent) behavior in order to enhance moral beliefs. However, to date, little is known about the effectiveness regarding recidivism and the subgoals of Halt. The aim of the current study is to determine the effectiveness of the Dutch diversion measure Halt. Methods A Randomized Controlled Trial (RCT) is conducted among 1,300 juveniles who are referred to Halt after committing a minor offence. They are randomized into the Halt condition, or into the control group with no further intervention. Self-report data on primary (delinquency) and secondary goals (subgoals of Halt, e.g., social skills) are collected at three points in time: after referral to Halt (T0), 100 days later (T1) and one year after the referral to Halt (T2). At T1 experienced compliance with children’s rights is also measured, given the importance of insight in the relation between compliance with children’s rights and the effectiveness of this diversionary measure. Several scales are used to conceptualize children’s rights aspects, such as the right to be heard and the right to legal assistance. To establish program integrity, Halt-employees fill out a questionnaire at T1. After two years, police and judiciary records are analyzed (T3). Characteristics of the participants, the employees and the execution of Halt are investigated as moderators. Discussion The results contribute to the limited knowledge about the effectiveness of diversion programs in general and Dutch juvenile justice more specifically. This knowledge adds to an evidence-based practice of criminal justice diversion in the Netherlands. Trail registration ClinicalTrials.gov #NCT06353204, retrospectively registered on April 4th, 2024.